1974
DOI: 10.1063/1.1663155
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of recombination in nitrogen-doped GaP

Abstract: The doping dependence of the bulk efficiency for both n- and p-type GaP:N has been investigated experimentally and theoretically. Experimental data are presented for p-type Zn,N-doped, n-type Te,N-doped, and n-type S,N-doped GaP over a majority-carrier range 5×1016−2×1018 cm−3. The efficiency data and photoluminescent decay time data on the same samples are compared to a simple equilibrium model for the recombination kinetics in nitrogen-doped GaP. The model predicts that the efficiency should scale linearly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The emission spectra of single crystal ZnO films are similar to the spectra of bulk ZnO crystals [20] and are comparable in emission intensity I, FWHM, and peak position λ max of the emission line.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…The emission spectra of single crystal ZnO films are similar to the spectra of bulk ZnO crystals [20] and are comparable in emission intensity I, FWHM, and peak position λ max of the emission line.…”
Section: Methodsmentioning
confidence: 71%
“…The following two processes involve a REI trap with excited intracenter states and an electron (hole) at a neutral donor (acceptor) [20]. An impor tant role is played by Auger quenching involving free carriers in wide gap semiconductors at high tempera tures and under laser excitation [20].…”
Section: Methodsmentioning
confidence: 99%
“…3, the PL intensity decreases with increasing the hole concentration corresponding to Mg concentration and thus it is considered that this quenching of the PL emission is caused by the nonradiative recombination centres due to Mg doping, when the hole concentration is larger than ~10 18 cm -3 . Dapkus et al [21] have reported the hole concentration dependence of the effective lifetime for Zn-doped p-type GaP:N grown by liquid-phase epitaxy, where the effective lifetime is reduced and PL quenching occurs due to the acceptor doping larger than ~10 18 cm -3 . Therefore, these results suggest that the hole concentration of p-type GaPN cladding layer surrounds the active layer should be less than ~10 18 cm -3 .…”
Section: Resultsmentioning
confidence: 98%
“…The steady-state luminescence intensity as function of temperature can be described using an excitonic recombination kinetic model, similar to the model proposed for n-type GaP:N [10]. The recombination shunt channel involving the broadband IR emission via D-deep level is described by the holes shunt-path capture time, t S (see the text that follows).…”
Section: Discussionmentioning
confidence: 99%